Didactic Possibilities Of Increasing Educational Motivation In Younger Students - Shodieva Matluba Juraevna (Genius Publishing Group, 2024)
This article highlights the didactic possibilities of increasing the educational motivation of primary school students. Motivational groups, ways and factors of increasing educational motivation are also described in detail.
Keywords: motive; educational motivation; sustainable motivation